Next-Generation Organoids: Redefining Human Disease Modeling and Drug Discovery - Nasser Atiya, Noor Al-Huda Abbas; Mardan Beck, Mayameen Talib; Ghanem Mohi, Zainab Hassoun; Jihadi Madhlom, Zahraa Hassan; Obeas Madhloom, Marwa Kadhim; Kadhim Jabid, Abbas Hamid (American Journal of Botany and Bioengineering, 2025)
Organoid technology models human tissues efficiently in vitro, preserving organ properties and functions. By recapitulating tissue architecture and physiology, organoids advance our understanding of human embryogenesis, tissue development, and disease. When combined with engineered platforms, patient-derived organoids transform biomedical research, accelerating preclinical assessments of candidate drugs. Patient-derived tumor organoids stand out as tools for exploring tumor-immune interactions and personalized medicine. Emerging application areas include genome and epigenome editing, antibody discovery, and transcriptomic analyses . The brief summarizes organoid technology, explores advances in organoid types and culture methodologies, and examines applications in disease modelling and drug discovery. Next-generation organoids combined with engineered substrates enable artificial tissues at centimetre scale with functional vasculature, facilitating large-scale production for a broad spectrum of human tissues. The review identifies key challenges and highlights future trends in the field.